Effect of Clinical, Endoscopic, Radiological Findings, and Complications on Survival in Patients with Primary Gastrointestinal Lymphoma - Erkut, Murat; Erkut, Nergiz; Bektaş, Özlen; Fidan, Sami; Coşar, Arif Mansur; Sönmez, Mehmet (Turkish Journal of Gastroenterology, 2022)
Background: The purpose of this study was to evaluate the clinical, endoscopic, and radiological characteristics, complications, survival outcomes, and prognostic factors of patients with primary gastrointestinal lymphoma. Methods: This study retrospectively analyzed the demographic, laboratory, endoscopic, and radiological characteristics and treatment outcomes of 43 patients with newly diagnosed primary gastrointestinal lymphoma. Results: The median age was 62 years (range: 26-83). The primary lesion location was the gastric in 33 (77%) patients and the intestinal in 10 (23%) patients. The most common lesions were the corpus (33%) and corpus+antrum (24%) in primary gastric lymphoma and the ileum (60%) in primary intestinal lymphoma. The most common endoscopic findings were diffuse infiltrative lesion (23%) and massforming (33%), while the most common computed tomography finding was wall thickening (53%). Wall thickening and mass-forming at computed tomography were greater in primary intestinal lymphoma than in primary gastric lymphoma (P = .034). Complications were observed in 9 (21%) patients and 13 (31%) patients who underwent surgery. Complication and surgery rates were higher in primary intestinal lymphoma than in primary gastric lymphoma (P = .003 and P = .014, respectively). Five-year overall survival and 5-year eventfree survival rates were 75% and 72%, respectively. Univariate analysis showed that intestinal involvement, advanced clinical stage, a high International Prognostic Index score, mass-forming and wall thickening at computed tomography, extranodal involvement, and complication were found to adversely affect survival. Multivariate analysis revealed that intestinal involvement and a high International Prognostic Index score were independent prognostic factors for overall survival and event-free survival. Conclusion: Patients with primary gastrointestinal lymphoma with intestinal involvement and high International Prognostic Index score should be followed closely.. Cite this article as: Erkut M, Erkut N, Bektaş Ö, Fidan S, Coşar AM, Sönmez M. Effect of clinical, endoscopic, radiological findings, and complications on survival in patients with primary gastrointestinal lymphoma. Turk J Gastroenterol. 2022;33(11):909-917.